Class, Mothering and the Values of Food - Aamann, Iben Charlotte (Kvinder, Køn & Forskning, 2017)
Class, Mothering and the Values of Food: The data analysed in this empirical paper stems from ethnographic fieldwork among new school parents at three Danish primary schools. I draw on empirically grounded theories on the cultural and subjective dimensions of class, inspired by the ‘English School’ of poststructuralist informed, feminist scholars, to explore how class matters. Using the values ascribed to food at social arrangements as a lens, I explore different ways of doing class and mothering: through the exchange values of the food, through its use value and through its healthiness. I conclude by arguing that food studies hold a huge potential for the development of empirically grounded theories on class in Scandinavian society, where class hitherto has been ascribed as a thing of the past.